ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN DEMAND ATAS PEMANFAATAN PENOLONG PERSALINAN DI PROVINSI BANTEN: ANALISIS DATA SUSENAS 2019 - Natalia Melani; Atik Nurwahyuni (Sekolah Tinggi Pariwisata Mataram, 2022)
Public health development is one of the important aspects in overall national development. In recent years the high maternal mortality rate (MMR) and infant mortality rate (IMR). The higher the maternal and infant mortality rates in a country, it can be ascertained that the health status of the country is poor. The purpose of this study was to examine the determinants of the use of birth attendants in Banten Province. This study uses a quantitative research design. The multivariate analysis used logistic regression with the econometric approach of the logit model. The sample was taken based on the inclusion criteria, namely status in the household as wife/mother, married woman, age 15-54 years old, had given birth to a live-born child and lived in Banten Province which was recorded in the 2019 Susenas. The results obtained were delivery assistance in the Banten Province. most (85.03%) have utilized health workers (midwives or doctors). The predisposing factors that were significantly related to the use of birth attendants in Banten Province were maternal age, number of children, maternal employment status and self-medication. The determinants of enabling factors that are significantly related to the use of birth attendants in Banten Province are economic status and ownership of health insurance. The variables of mother's education level, husband's education level, husband's employment status, area of ​​residence, savings ownership, electronic media ownership, home ownership status and access to the internet were not significantly related to the use of birth attendants in Banten Province. The most dominant variable related to the use of birth attendants in Banten Province is the number of children with OR = 4.3448, P value = 0.000.